2022
DOI: 10.1111/cdev.13885
|View full text |Cite
|
Sign up to set email alerts
|

Association between prenatal maternal anxiety and/or stress and offspring's cognitive functioning: A meta‐analysis

Abstract: This meta‐analysis examined the relationship between prenatal maternal stress and/or anxiety and the outcomes of children aged 3 months to 9 years. Of the 8754 studies published before June 2021 that were synthesized, 17 conducted in Western countries were included in the meta‐analysis (Ntotal = 23,307; Mmales 54%; Methnicity White 77%, Pacific 15%, African American/Black 10%, Middle Eastern 7%, Eastern 8%). Effect sizes ranged from −0.41 to 0.15. A weak negative association was found between prenatal stress a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 124 publications
0
5
0
Order By: Relevance
“…Recent meta-analyses have found associations between in utero exposure to maternal distress and (self-)regulation problems at the cognitive, behavioral and social-emotional level, that is, for: (i) postpartum bonding problems [with depression ( r = 0.20 to 0.25), anxiety ( r = 0.16), stress ( r = 0.15) and preconception stress ( r = −0.17)] [62]; (ii) internalizing problems in infancy (associated with maternal internalizing ( r = 0.17) as well as with paternal internalizing problems ( r = 0.13) [63]; (iii) cognitive problems in infancy and childhood , for example, cognitive problems (neonates–60 months) ( r = −0.05) [64], lower executive function (6 months–9 years ( r = 0.07) [65], lower general cognitive ability (3 months- 9 years) (effect sizes between −0.041 to 0.15) [66]; (iv) social-emotional and behavioral problems including emotional dysregulation, aggressive behavior, internalizing and externalizing problems) in infancy and childhood ( r = 0.16) (2 months–8.5 years) [67 ▪▪ ]; (v) negative socio-emotional and cognitive outcome from infancy to late adolescence : social-emotional problems (2 months–17 years) (OR = 1.66), more so in depression than anxiety [68]; motor ( r = −0.07), cognitive ( r = −0.12), language ( r = −0.11), social-emotional ( r = 0.21), and adaptive behavior ( r = −0.26) (4 weeks–17 years) [69]; poorer cognitive outcomes only for boys (infancy to 18 years) [boys; Hedges’ g = −0.36, girls: Hedges’ g : = −0.17) and outcome was poorer when a diagnostic interview was used compared to the use of a rating scale [70]. (vi) Finally, one meta-analysis included psychopathological outcome : increased risk of both ASD (pooled OR 1.64) and ADHD (pooled OR 1.72) was confirmed in a meta-analysis including 2–27 year old offspring [71].…”
Section: Perinatal Mental Health and Offspring Outcome: Results Mecha...mentioning
confidence: 99%
“…Recent meta-analyses have found associations between in utero exposure to maternal distress and (self-)regulation problems at the cognitive, behavioral and social-emotional level, that is, for: (i) postpartum bonding problems [with depression ( r = 0.20 to 0.25), anxiety ( r = 0.16), stress ( r = 0.15) and preconception stress ( r = −0.17)] [62]; (ii) internalizing problems in infancy (associated with maternal internalizing ( r = 0.17) as well as with paternal internalizing problems ( r = 0.13) [63]; (iii) cognitive problems in infancy and childhood , for example, cognitive problems (neonates–60 months) ( r = −0.05) [64], lower executive function (6 months–9 years ( r = 0.07) [65], lower general cognitive ability (3 months- 9 years) (effect sizes between −0.041 to 0.15) [66]; (iv) social-emotional and behavioral problems including emotional dysregulation, aggressive behavior, internalizing and externalizing problems) in infancy and childhood ( r = 0.16) (2 months–8.5 years) [67 ▪▪ ]; (v) negative socio-emotional and cognitive outcome from infancy to late adolescence : social-emotional problems (2 months–17 years) (OR = 1.66), more so in depression than anxiety [68]; motor ( r = −0.07), cognitive ( r = −0.12), language ( r = −0.11), social-emotional ( r = 0.21), and adaptive behavior ( r = −0.26) (4 weeks–17 years) [69]; poorer cognitive outcomes only for boys (infancy to 18 years) [boys; Hedges’ g = −0.36, girls: Hedges’ g : = −0.17) and outcome was poorer when a diagnostic interview was used compared to the use of a rating scale [70]. (vi) Finally, one meta-analysis included psychopathological outcome : increased risk of both ASD (pooled OR 1.64) and ADHD (pooled OR 1.72) was confirmed in a meta-analysis including 2–27 year old offspring [71].…”
Section: Perinatal Mental Health and Offspring Outcome: Results Mecha...mentioning
confidence: 99%
“…Strong evidence for sex moderating associations between prenatal stress exposure and cognitive outcomes from animal models (Glover & Hill, 2012) does not seem to extend to humans. In fact, a recent meta-analysis of 22 studies observed a modest negative association between maternal stress and anxiety (a proxy for HPA axis physiology) and cognitive outcomes but did not observe any moderation by sex (Delagneau et al, 2023). Further research that incorporates prenatal sex steroids and other plausible explanations for sex moderation is needed to advance this line of research in humans.…”
Section: Discussionmentioning
confidence: 99%
“…We replicated and extended the study of Madigan et al with a larger sample size, at a slightly early age, and with differential cultural backgrounds. Maternal prenatal or postpartum stress and child’s sex may be associated with cognitive functioning and behavioral problems in children . Detecting interactions is crucial for public health if maternal stress influences the fetal or children’s environment.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal prenatal or postpartum stress and child’s sex may be associated with cognitive functioning and behavioral problems in children. 21 , 22 , 23 , 24 , 25 , 26 Detecting interactions is crucial for public health if maternal stress influences the fetal or children’s environment.…”
Section: Introductionmentioning
confidence: 99%